Usefulness of CT for diagnosis of breast malignancy metastasis variants to the vertebrae - Yousif, Raaid T.; Bondarenko, Igor; Fiodorovna, Tatiana (Menopause Review/Przegląd Menopauzalny, 2012)
Objectives: Breast cancer is the most common malignancy in women. A clinical state of the patient depends on the stage of cancer and the existing metastases. Breast cancer tends to have venous metastases and the bones are one of the most frequent localization of the lesions. Aim of study : The aim of the study was to investigate breast cancer (CA) metastases with respect to the type and anatomical localization Special attention was paid to metastases to the vertebrae. Material and methods : The patients with diagnosed CA in stage IV had been involved into the study. A preferable localization of the metastatic lesion in the single spine element and a histopathological type of the lesions were analyzed. The study involved 143 patients treated in the Dnepropetrovsk 4th hospital, Department of Surgery. All the patients underwent CT examination of the spine. Results: Most of the metastatic lesions were of the osteolytic type and were localized in the thoracic spine.